Reforming China’s Criminal Procedure: An Introduction to This Symposium - Cohen, Jerome A. (Columbia Journal of Asian Law, 2011)
On August 30, 2011, the Standing Committee of China’s National People’s Congress published comprehensive and significant draft amendments to the nation’s Criminal Procedure Law and sought public comments on the proposed revisions. According to China’s legislative process, it is likely that the National People’s Congress will vote on some version of these proposed amendments during its annual meeting in March 2012. The articles in this volume reflect, analyze, and discuss the state of Chinese criminal procedure law before the publication of the proposed amendments. Accordingly, they set the stage for the current round of legislative reform, which has aroused great interest both within China and abroad. Once the amendments become law, this will no doubt create an opportunity and perhaps an imperative to revisit the issues examined in this volume and to evaluate what has and has not been amended and the effect of those changes. We are happy to play a role in this important process.